PENGARUH EKONOMI GIG TERHADAP KINERJA DAN PRODUKTIVITAS GEN Z - Muhammad Ilham Yusuf; Sumule, Brigita Meys; felicia, felicia; Wijaya, Maheswara Atma; Winata, I Made Wira Marciano; Aryusmar, Aryusmar (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2026)
This study aims to analyse the impact of the Gig economy on Generation Z (Gen Z) performance and productivity using a mixed methods approach that combines qualitative and quantitative methods. The Gig economy, with its flexibility and short-term nature of projects, is increasingly popular among Gen Z, yet its impact on productivity has not been thoroughly researched.The qualitative method was conducted through semi-structured interviews with 10 Gen Z respondents who work as freelancers, online drivers, and temporary project workers. Respondents were selected using purposive sampling to ensure data relevance. The interviews explored motivations, challenges, and the impact of the gig economy on time management, performance, and productivity. Data was analysed using thematic techniques to find key patterns.In the quantitative method, a Likert scale questionnaire was distributed to 100 respondents selected by simple random sampling. The questionnaire measured two independent variables, namely flexibility and work duration, and two dependent variables, namely performance and productivity. Simple linear regression test was used to identify the relationship between these variables.The results showed that Gig economy has a significant influence on Gen Z's performance and productivity. Qualitatively, work flexibility increases motivation, while challenges such as time management and income uncertainty can decrease productivity. Quantitatively, flexibility has a positive relationship with performance, while long work duration tends to negatively impact productivity.This research provides an in-depth insight into the Gig economy and its implications for Gen Z. The results are expected to serve as a reference for policy makers and industry players to create a work ecosystem that better supports the productivity and well-being of gig workers.